Qualité De La Formation Et Des Enseignements Dispensés Par Les Instituteurs Ordinaires Et Les Instituteurs Adjoints : Points De Vue Des Professeurs Des Cafop Et Des Conseillers Pédagogiques Des Secteurs De L’enseignement Primaire - Coulibaly Abdoulaye (European Scientific Journal, ESJ, 2018)
Good teacher training is one of the keys to ensuring that students receive good quality of teaching. Due to economic reasons in Ivory Coast, there has been a massive recruitment of teachers with a lower quality of educational training compared to what was previously considered. As a result, several questions about the quality of the lessons have emerged. However, this paper focuses on collecting the points of view of the CAPT teachers (Center for Animation and Pedagogical Training) and the educational advisers to the primary educational sectors in regards to the quality of training and the teaching provided by assistant teachers and ordinary teachers. In Ivory Coast, it is the CAPTs who trains the teachers who teaches in primary schools. The answers collected and analyzed allow us to conclude that although these two types of teachers have almost identical training, the level of the quality of the teaching provided by the assistant teachers is lower than that of the ordinary teachers. The general training acquired before becoming part of this body of teachers appears as the main reason for this difference.